3D printing of high entropy alloys (HEAs) by directed energy deposition (DED) - Lim, Sharie Yun (Nanyang Technological University, 2022)
Additive Manufacturing (AM) processes enable users to design and create 3D printed models by using Computer-Aided-Design (CAD) software and converting them into stereolithography (STL) file for the 3D printer to recognise. In doing so, much of the disadvantages associated with traditional manufacturing are eliminated providing new pathways for sustainable and efficient design. AM techniques, notably Directed Energy Deposition (DED) reduce the cost for repairing and manufacturing of components, since the need for expensive tools associated with traditional manufacturing for the creation of higher complexity parts are removed. With increased complexity of parts made and material used, comes the challenge of optimising the materials to fully utilize their potential in building specific parts. Hence, process parameters are required for optimisation of materials especially for more novel materials that are less often handled or tested. Additionally, such process parameters can be documented for further analysis when dealing with elements of similar nature. High Entropy Alloys (HEAs) enables the exploration of different combinations of elements since it allows the combination of multiple elements, which produces different variation of alloys that were not possible for conventional alloy. Thus, leading to the discovery of alloys with versatility and flexibility based on the design requirements. In the research work detailed in this report, a powder-based DED technique is utilized to fabricate a Cobalt Chromium Iron Nickel (CoCrFeNi) HEA and develop a process parameter window for the treatment of the alloy using a variety of process parameters for the DED of HEAs. The process parameter window will be the first step towards tailoring the microstructure of additively manufactured HEAs. The process parameter will be optimised through the fabrication of thin wall to demonstrate the mechanical properties and thin wall structure.